Method for treating and recovering spent nitric acid
Patent Information
- Application Number
- CN202611102155.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]现有扩散渗析酸回收技术多依赖阴离子交换膜的固定正电荷基团实现酸根迁移,并利用金属阳离子水合半径和电荷差异形成阻隔,但在高硝酸浓度和复杂金属离子共存环境中,膜的酸传质、金属离子截留和长期耐酸稳定性常难以同步提高
1.通过采用交联聚苯并咪唑基体和咪唑鎓化区域相结合的中空纤维结构,使耐酸骨架提供膜体支撑,咪唑鎓基团提供酸根迁移位点,从而降低单纯提高交联程度导致酸传质受阻的风险,并改善单纯提高离子化程度导致结构稳定性下降的问题。
Smart Images

Figure CN122916282A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of waste acid membrane separation and recycling technology, specifically to a method for treating and recycling waste nitric acid. Background Technology
[0002] Processes such as stainless steel pickling, metal surface treatment, post-nitration washing, and electronic chemical cleaning generate waste nitric acid solutions containing nitric acid and various metal ions. These solutions typically exhibit strong acidity, large fluctuations in metal salt content, strong oxidizing properties, and high corrosiveness. Direct neutralization not only consumes large amounts of alkali solution but also forms metal-containing sludge, increasing the pressure on subsequent resource recovery and volume reduction. Direct reuse, on the other hand, can easily affect the quality of pickling or cleaning due to the accumulation of metal ions. Diffusion dialysis utilizes the concentration difference across a membrane to achieve selective migration of acid and salt. It features low energy consumption, a relatively simple process, and suitability for continuous operation, thus possessing application value in the field of waste acid resource recovery. For waste nitric acid systems, membrane materials need to maintain sufficient acid mass transfer capacity while effectively blocking divalent or trivalent metal ions. Furthermore, they must maintain structural integrity, dimensional stability, and low flux decay under long-term acidic environments and hollow fiber module operation conditions. This places higher demands on membrane material structural design and process window. The basic principles and industrial application value of diffusion dialysis for acid recovery have been widely discussed in published literature.
[0003] Existing diffusion dialysis acid recovery technologies largely rely on the fixed positively charged groups of anion exchange membranes to achieve acid anion migration and utilize the hydration radius and charge difference of metal cations to form barriers. However, in environments with high nitric acid concentrations and complex metal ion coexistence, it is often difficult to simultaneously improve the membrane's acid mass transfer, metal ion retention, and long-term acid resistance. For example, Chinese patent CN103962020A discloses a diffusion dialysis membrane for acid recovery, its preparation method, and its application. Its background section points out that diffusion dialysis is a concentration gradient-based membrane separation process and focuses on the application of anion exchange membranes for acid recovery. However, this type of membrane system still needs to address the comprehensive balance issue of acid recovery efficiency, membrane strength, corrosion resistance, and industrial operability. Another disclosed scheme for the recovery of nitric acid and hydrofluoric acid from stainless steel pickling wastewater combines diffusion dialysis with a subsequent electro-membrane process, indicating that the acid form, metal salts, and complex components in complex pickling wastewater affect the recovery efficiency of a single diffusion dialysis step. Therefore, there is still a need to develop hollow fiber membrane module treatment routes that take into account structural integrity, processing fluidity, nitric acid recovery, and metal ion retention. Summary of the Invention
[0004] The purpose of this invention is to provide a method for treating and recycling waste nitric acid, which solves the current pain point of diffusion dialysis membranes in balancing structural integrity, nitric acid recovery, processing fluidity, and metal ion retention.
[0005] Existing methods for improving the structural integrity of hollow fibers often enhance cross-linking constraints and hinder nitric acid mass transfer, while increasing the degree of ionization may weaken membrane stability. This invention achieves a synergistic balance between two naturally contradictory properties by matching the cross-linked polybenzimidazole matrix, the imidazole-encapsulated region, and the countercurrent diffusion dialysis conditions, thereby mutually correcting structural constraints, acid mass transfer, and metal ion barrier.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for treating and recycling waste nitric acid includes the following steps: S1, providing waste nitric acid solution, wherein the mass fraction of nitric acid in the waste nitric acid solution is 5-45 wt%, and the mass fraction of total metal ions based on metal elements is 0.05-15 wt%, wherein the total metal ions include at least one selected from divalent metal ions and trivalent metal ions; S2, the waste nitric acid feed solution is brought into contact with the feed side of the diffusion dialysis membrane module, and tap water is brought into contact with the dialysis side of the diffusion dialysis membrane module. The hollow fiber in the diffusion dialysis membrane module is obtained by polybenzimidazole, which is obtained by polycondensation of 3,3′-diaminobenzidine and isophthalic acid in polyphosphoric acid medium, crosslinked with 1,4-di(bromomethyl)benzene, bromobutylated with 1,4-dibromobutane, and further reacted with 1-methylimidazole. The content of imidazole onium groups in the hollow fiber is 0.30-1.20 mmol / g. S3 controls the processing temperature to be 20-45℃, the linear velocity of the feed liquid to be 0.20-1.00m / s, and the absolute value of the pressure difference between the dialysis side and the feed liquid side to be 0.01-0.15MPa, and uses a countercurrent method for mass transfer; S4, collect and recover acid solution and metal-rich residue solution respectively.
[0007] The waste nitric acid solution originates from at least one of the processes of stainless steel pickling, metal surface treatment, post-nitration washing, or electronic chemical cleaning.
[0008] Furthermore, the waste nitric acid solution is pre-filtered before step S1, with a filtration accuracy of 1-100 μm; the mass flow ratio of tap water to waste nitric acid solution in step S2 is 1:1-6:1; steps S2 and S3 are carried out in the primary diffusion dialysis unit.
[0009] Furthermore, after the diffusion dialysis membrane module has been running continuously for 12-72 hours, it is regenerated by rinsing with tap water at 20-40°C for 10-60 minutes.
[0010] Furthermore, the nitric acid recovery rate in step S4 is 70-95%, and the total metal ion removal rate is 60-95%; when the treatment and recovery method is continuously operated for 100-500 hours, the flux decay rate of the diffusion dialysis membrane module is not higher than 20%.
[0011] Furthermore, the diffusion dialysis membrane assembly used in step S2 includes a membrane shell and a hollow fiber membrane bundle disposed within the membrane shell. The hollow fiber membrane bundle is composed of multiple hollow fibers. Each hollow fiber includes a cross-linked polybenzimidazole matrix and an imidazole-encapsulated region covalently bonded to the cross-linked polybenzimidazole matrix. The hollow fiber has an inner diameter of 300-700 μm, a wall thickness of 100-220 μm, an imidazole-encapsulated group content of 0.30-1.20 mmol / g, and a water content of 7.0-17.0 wt%.
[0012] Furthermore, the hollow fiber has an average pore size of 3-25 nm, a porosity of 15-45%, a water absorption rate of 8.0-20.0 wt%, and a burst pressure of 0.20-1.20 MPa; the thickness of the imidazole-encapsulated region is 20-120 nm; the effective membrane area of the diffusion dialysis membrane module is 0.1-20.0 m², and the membrane bundle packing density is 20-60%.
[0013] In this specification, the linear velocity on the feed side is the ratio of the volumetric flow rate of the waste nitric acid feed to the effective flow cross-sectional area on the feed side; the mass flow rate ratio of tap water to waste nitric acid feed is the ratio of the mass of tap water entering the dialysis side per unit time to the mass of waste nitric acid feed entering the feed side per unit time; the effective membrane area is the wall area of the hollow fiber membrane bundle that participates in mass transfer between the feed side and the dialysis side; and the membrane bundle packing density is the ratio of the sum of the outer diameter cross-sectional areas of each hollow fiber in the hollow fiber membrane bundle to the cross-sectional area of the inner cavity of the membrane shell.
[0014] Furthermore, the polybenzimidazole resin, the raw material for the hollow fiber, is prepared through the following steps: A1 is prepared by mixing 100 parts by weight of 3,3′-diaminobenzidine, 90-110 parts by weight of isophthalic acid, and 600-1200 parts by weight of polyphosphoric acid. A2 undergoes polycondensation at 180-220℃ for 6-14 hours under industrial nitrogen protection; A3. Pour the reaction product into deionized water to precipitate polybenzimidazole, and wash until the pH of the washing solution is 6-7. A4 was dried at 80-120℃ and under a vacuum degree not exceeding -0.08MPa for 8-24 hours to obtain polybenzimidazole resin with an intrinsic viscosity of 1.0-2.5dL / g.
[0015] Furthermore, cross-linked polybenzimidazole hollow fibers are prepared through the following steps: B1, dissolve the polybenzimidazole resin in N,N-dimethylacetamide to prepare a spinning solution with a polybenzimidazole mass fraction of 15-22 wt%, and degas for 1-8 hours; B2 is produced by dry-jet wet spinning under the following conditions: deionized water as the core liquid, spinning pressure of 0.05-0.30 MPa, air gap of 5-25 cm, coagulation bath of deionized water at 15-35 ℃, and traction speed of 3-5 m / min. B3, the polybenzimidazole hollow fibers are washed in deionized water until the residual N,N-dimethylacetamide is not higher than 1.0 wt%; B4, the washed polybenzimidazole hollow fibers are impregnated in a solution of N,N-dimethylacetamide containing 1,4-di(bromomethyl)benzene and reacted at 60-90°C for 1-6 hours under industrial nitrogen protection; B5 is washed and dried at 40-80℃ and a vacuum degree not higher than -0.08MPa for 4-24h to obtain cross-linked polybenzimidazole hollow fibers.
[0016] Furthermore, the imidazole-enhanced region is formed through the following steps: C1, the cross-linked polybenzimidazole hollow fiber is impregnated in an N,N-dimethylacetamide solution containing 1,4-dibromobutane and reacted at 50-90°C for 1-8 hours under industrial nitrogen protection to introduce bromobutyl; C2, the cross-linked polybenzimidazole hollow fibers treated in step C1 are transferred to an N,N-dimethylacetamide solution containing 1-methylimidazole and reacted at 40-80°C for 2-12 hours to quaternize; C3, wash the cross-linked polybenzimidazole hollow fibers treated in step C2 until the bromide ion concentration in the washing solution is not higher than 50 mg / L; C4 is dried at 40-80℃ and a vacuum degree not higher than -0.08MPa for 4-24h to obtain imidazole-onthiolated crosslinked polybenzimidazole hollow fibers.
[0017] All vacuum levels mentioned in this manual are gauge pressures.
[0018] Furthermore, in step B4, the molar ratio of 1,4-di(bromomethyl)benzene to benzimidazole NH in the polybenzimidazole hollow fiber before the reaction in step B4 is 0.02:1-0.20:1; in step C1, the molar ratio of 1,4-dibromobutane to benzimidazole NH in the crosslinked polybenzimidazole hollow fiber before the reaction in step C1 is 0.05:1-0.50:1; and in step C2, the molar ratio of 1-methylimidazole to the bromobutyl group introduced in step C1 is 1.0:1-3.0:1.
[0019] Further, the waste nitric acid solution, recovered acid solution, and metal-rich residual solution are weighed and diluted to a fixed volume to obtain test samples. The actual mass concentrations of metal elements present in Fe, Cr, Ni, Al, Cu, Zn, Mn, and Ti are determined by inductively coupled plasma atomic emission spectrometry or inductively coupled plasma mass spectrometry. The total metal element mass concentration is obtained by summing the mass concentrations of each metal element. The total metal ion mass or mass fraction is then calculated by combining the mass or volume of the corresponding sample. The conversion results are used to calculate the composition of the solution and the total metal ion removal rate in step S1.
[0020] Furthermore, the nitric acid recovery rate is calculated by multiplying the ratio of the mass of nitric acid in the recovered acid solution to the mass of nitric acid in the waste nitric acid solution by 100%. The total metal ion removal rate is calculated by multiplying the ratio of the difference between the total mass of metal ions in the waste nitric acid solution (calculated as metal elements) and the total mass of metal ions in the recovered acid solution (calculated as metal elements) to the total mass of metal ions in the waste nitric acid solution by 100%. The flux decay rate of the diffusion dialysis membrane module is calculated by multiplying the ratio of the difference between the initial flux and the flux after continuous operation to the initial flux by 100%. The initial flux and the flux after continuous operation are measured under the same conditions of waste nitric acid solution composition, treatment temperature, feed liquid side linear velocity, absolute value of the pressure difference between the dialysis side and the feed liquid side, and mass flow ratio of tap water to waste nitric acid solution. The corresponding mass or volume of the waste nitric acid solution, recovered acid solution, and metal-rich residue is recorded when calculating the mass of nitric acid and the total metal ion mass.
[0021] Furthermore, during dry-jet wet spinning, the polybenzimidazole spinning solution and the deionized water used as the core solution enter the annular channel and core solution channel of the coaxial spinneret, respectively. The polybenzimidazole spinning solution enters the 15-35℃ deionized water coagulation bath through a 5-25cm air gap. The core solution forms an inner coagulation interface on the inner side of the fiber cavity. After coagulation, the polybenzimidazole hollow fiber is washed with deionized water and then enters the residual N,N-dimethylacetamide control step. The coagulated polybenzimidazole hollow fiber is collected at a traction speed of 3-5m / min.
[0022] Furthermore, when detecting solvent residue in the polybenzimidazole hollow fibers after washing in step B3, the polybenzimidazole hollow fiber sample is extracted with deionized water to obtain an extract. The N,N-dimethylacetamide content in the extract is determined by gas chromatography or high performance liquid chromatography. The residual N,N-dimethylacetamide content is calculated based on the ratio of the mass of extracted N,N-dimethylacetamide to the mass of the polybenzimidazole hollow fiber sample before extraction. Polybenzimidazole hollow fibers with a residual N,N-dimethylacetamide content not exceeding 1.0 wt% proceed to step B4.
[0023] Furthermore, the N,N-dimethylacetamide solutions used in steps B4, C1, and C2 are prepared before the corresponding reactions. In step B4, the crosslinking reaction solution is prepared with a molar ratio of 1,4-di(bromomethyl)benzene to benzimidazole NH in the polybenzimidazole hollow fiber before the reaction in step B4 of 0.02:1-0.20:1. In step C1, the bromobutylation reaction solution is prepared with a molar ratio of 1,4-dibromobutane to benzimidazole NH in the crosslinked polybenzimidazole hollow fiber before the reaction in step C1 of 0.05:1-0.50:1. In step C2, the quaternization reaction solution is prepared with a molar ratio of 1-methylimidazole to the bromobutyl group introduced in step C1 of 1.0:1-3.0:1. Each reaction solution uses N,N-dimethylacetamide as a solvent and is used to impregnate the corresponding hollow fiber reaction object.
[0024] Further, after step C1, the bromobutylated cross-linked polybenzimidazole hollow fibers are divided into a first test sample and a second reaction sample. The bromine content of the first test sample is detected and the amount of free bromide ions carried out by the washing solution is deducted to obtain the bromobutyl content introduced into the fiber. The second reaction sample is added with 1-methylimidazole according to the measured bromobutyl content to carry out the quaternization reaction in step C2. The hollow fibers after the quaternization reaction are then washed in step C3.
[0025] Furthermore, when determining the imidazolium group content of the imidazolium-crosslinked polybenzimidazole hollow fibers obtained in step C4, the dried hollow fiber sample is subjected to ion exchange treatment to allow the exchangeable anions of the imidazolium group to enter the exchange solution. The amount of anions in the exchange solution is determined by silver nitrate titration or ion chromatography. The imidazolium group content is calculated based on the ratio of the amount of anions to the mass of the dried hollow fiber sample, and the calculated imidazolium group content is used as the structural control index of the hollow fibers used in step S2.
[0026] Furthermore, when measuring the thickness of the imidazole-intumescent region of the imidazole-intumescent crosslinked polybenzimidazole hollow fiber obtained in step C4, a cross-sectional sample of the hollow fiber was taken for transmission electron microscopy line scanning or X-ray photoelectron spectroscopy depth analysis. The distribution data of N and Br elements along the wall thickness direction of the hollow fiber were recorded. The region where the N and Br element signals changed continuously relative to the unimidazole-intumescent internal region was taken as the imidazole-intumescent region, and the size of this region along the wall thickness direction was taken as the thickness of the imidazole-intumescent region.
[0027] Furthermore, when determining the moisture content and water absorption of the imidazole-onyl crosslinked polybenzimidazole hollow fibers obtained in step C4, the hollow fiber samples after being vacuum dried at 40-80℃ for 4-24h are recorded as dry samples and their dry mass is weighed. The dry samples are then immersed in deionized water at 25℃ for 24h, removed, and the surface is gently wiped with filter paper until no obvious liquid film is visible. The wet mass is then weighed. The moisture content is calculated by multiplying the ratio of the difference between the wet mass and the dry mass to the wet mass by 100%, and the water absorption rate is calculated by multiplying the ratio of the difference between the wet mass and the dry mass to the dry mass by 100%.
[0028] Furthermore, when determining the average pore size and porosity of the imidazole-onyl crosslinked polybenzimidazole hollow fibers obtained in step C4, the dried hollow fiber sample was used as the test object. The pore size distribution data was obtained by nitrogen adsorption-desorption method, and the average pore size was calculated based on the pore size distribution data. The pore volume data was obtained by impregnation and weighing method, and the porosity was calculated based on the ratio of the pore volume data to the apparent volume of the hollow fiber. The obtained average pore size and porosity were used to characterize the mass transfer channels of the hollow fiber.
[0029] Furthermore, when measuring the burst pressure of the imidazole-onyl crosslinked polybenzimidazole hollow fibers obtained in step C4, the two ends of the hollow fibers are sealed to form a single fiber test piece. Water or nitrogen is introduced into the inner cavity of the fiber and the pressure is continuously increased. The pressure value when the fiber wall ruptures is recorded as the burst pressure. The burst pressure data is used to screen hollow fibers entering the diffusion dialysis membrane module assembly step, and the burst pressure of the hollow fibers entering the diffusion dialysis membrane module is not lower than the absolute value of the pressure difference between the dialysis side and the feed liquid side during diffusion dialysis treatment.
[0030] Furthermore, when determining the intrinsic viscosity of the polybenzimidazole resin obtained in step A4, the polybenzimidazole resin sample, which had been vacuum dried at 80-120℃ for 8-24 hours, was dissolved in N,N-dimethylacetamide to form a polymer test solution. The outflow time of the polymer test solution and blank N,N-dimethylacetamide was measured at 25℃ using an Ubbelohde viscometer. The concentration of the polymer test solution, the test temperature, the polymer outflow time, and the blank solvent outflow time were recorded. The intrinsic viscosity of the polybenzimidazole resin was calculated using the dilution extrapolation method.
[0031] As a concept of this invention, the present invention employs the design of an imidazolium-crosslinked polybenzimidazole hollow fiber diffusion dialysis membrane module, primarily aimed at achieving a synergistic balance between the structural integrity of the hollow fiber and selective nitric acid mass transfer. In existing technologies, to improve the acid resistance and mechanical stability of the membrane, the degree of crosslinking is typically increased or the membrane wall density is improved. However, this strengthens chain segment constraints and compresses mass transfer channels, hindering nitric acid migration. To improve nitric acid recovery performance, the degree of ionization is typically increased or more ion transport sites are introduced. However, excessive ionization increases water absorption and swelling tendency, weakening the structural stability of the hollow fiber during continuous operation. This invention utilizes 1,4-bis(bromomethyl)benzene crosslinking, 1,4-dibromobutane bromobutylation, and 1-methylimidazolium reaction to form an adjustable imidazolium-crosslinked region. Combined with countercurrent mass transfer, linear velocity, water-to-material mass flow ratio, and absolute pressure difference control, the inhibitory effect of structural constraints on swelling and the promoting effect of imidazolium groups on acid anion migration mutually correct each other, thereby achieving a balance between acid recovery, metal ion barrier, and continuous operation stability.
[0032] As another concept of this invention, it employs a design that limits the composition of waste nitric acid feed solution and matches its source scenario, primarily to achieve, fix, or amplify the aforementioned synergistic effects. The mass fraction of nitric acid and the total mass fraction of metal ions (calculated as metal elements) in the waste nitric acid feed solution directly determine the concentration difference across the diffusion dialysis membrane, the difficulty of metal ion hydration and migration, and the acid corrosion pressure on the membrane material. If optimization is only applied to low-acid, low-salt systems, the membrane module may lack adaptability in acid washing or electronic cleaning waste liquids; if membrane wall density is only improved for high-acid, high-salt systems, processing flowability and nitric acid mass transfer may be sacrificed. This invention limits the waste nitric acid feed solution to industrial-sourced feed solutions containing nitric acid and at least one divalent or trivalent metal ion, and covers its sources in stainless steel acid washing, metal surface treatment, post-nitration washing, and electronic chemical cleaning processes, enabling the structural design, mass transfer conditions, and metal ion retention targets of the diffusion dialysis membrane module to function synergistically under actual waste liquid compositions.
[0033] The cross-linked polybenzimidazole matrix primarily addresses the structural integrity and operational stability of hollow fibers in acidic waste nitric acid solutions, while the imidazole-encapsulated region mainly addresses nitric acid mass transfer and selective metal ion separation. While the cross-linked polybenzimidazole matrix, if present alone or with excessively strong cross-linking constraints, helps maintain membrane wall morphology and burst pressure, it weakens nitric acid recovery due to restricted chain segment movement, pore shrinkage, and insufficient ion migration sites. Conversely, while the imidazole-encapsulated region, if strengthened alone or with excessively high content, facilitates acid anion migration and hydrophilic mass transfer, it negatively impacts structural integrity, long-term flux stability, and metal ion retention due to enhanced water absorption and localized swelling. This invention achieves a balance between the acid-resistant framework, adjustable ion sites, and hollow fiber pore structure through sequential control of 1,4-di(bromomethyl)benzene cross-linking, 1,4-dibromobutane bromobutylation, and 1-methylimidazolium quaternization. This balances the inherently contradictory properties of structural integrity versus nitric acid recovery and processing fluidity versus metal ion retention.
[0034] Beneficial technical effects 1. By adopting a hollow fiber structure that combines a cross-linked polybenzimidazole matrix and an imidazole-onium region, the acid-resistant skeleton provides membrane support, and the imidazole-onium groups provide acid radical migration sites. This reduces the risk of acid mass transfer being hindered by simply increasing the degree of cross-linking, and improves the problem of structural stability decreasing by simply increasing the degree of ionization.
[0035] 2. By controlling the composition of nitric acid and total metal ions in the waste nitric acid feed solution, the treatment temperature, the linear velocity of the feed solution side, the absolute value of the pressure difference between the dialysis side and the feed solution side, the mass flow ratio of tap water to waste nitric acid feed solution, and the countercurrent mass transfer method, the concentration difference, residence time, and pressure disturbance on both sides of the membrane can be matched, which is beneficial to improving the nitric acid recovery rate and reducing the risk of metal ions entering the recovered acid solution.
[0036] 3. By limiting the inner diameter, wall thickness, average pore size, porosity, water content, water absorption, burst pressure, and imidazolium-encapsulated region thickness within a coordinateable structural window, hollow fibers can maintain good wet strength while having mass transfer channels, making them suitable for continuous operation and periodic tap water rinsing and regeneration.
[0037] 4. By setting up methods for determining total metal ion content, nitric acid recovery rate, total metal ion removal rate, and flux decline rate in the instruction manual, a corresponding relationship can be established between the composition of the feed solution, the quality of the recovered acid solution, and the long-term operating status, which is beneficial to improving the repeatability and consistency of the treatment results evaluation.
[0038] 5. By refining the polybenzimidazole polycondensation, dry-jet wet spinning, crosslinking, bromobutylation and quaternization steps into controllable temperature, time, pressure, air gap, coagulation bath, traction speed, vacuum degree and molar ratio conditions, the uncertainty of hollow fiber forming and surface ionization processes is reduced, which facilitates industrial expansion and batch-to-batch quality control. Attached Figure Description
[0039] Figure 1 The graph shows the effect of imidazolium group content on nitric acid recovery and total metal ion removal under the conditions of Example 1 and the control.
[0040] Figure 2 The graph shows the effect of the water-to-material mass flow rate ratio on nitric acid recovery and total metal ion removal under the conditions of Example 1 and the control.
[0041] Figure 3 The graph shows the effect of treatment temperature on nitric acid recovery rate and total metal ion removal rate under the conditions of Example 1 and the control.
[0042] Figure 4 The graph shows the effect of the crosslinking agent molar ratio on the nitric acid recovery rate and total metal ion removal rate under the conditions of Example 1 and the control.
[0043] Figure 5 The graph shows the determination of imidazolium group content in Examples 1, 9, and 10.
[0044] Figure 6 The distribution of Br element along the wall thickness direction of hollow fiber is shown in Example 1 and Comparative Example 10.
[0045] Figure 7 The distribution of N element along the wall thickness direction of hollow fibers is shown in Example 1 and Comparative Example 10.
[0046] Figure 8 The diagram shows the differential pore size distribution of hollow fibers in Example 1, Comparative Example 7, and Comparative Example 8.
[0047] Figure 9 The cumulative pore size distribution of hollow fibers in Example 1, Comparative Example 7, and Comparative Example 8 is shown.
[0048] Figure 10 The images show the porosity test results of hollow fibers in Examples 1, 7, and 8.
[0049] Figure 11 The graphs show the moisture content test results of hollow fibers in Examples 1, 7, and 8.
[0050] Figure 12 The graphs show the water absorption rate test results of hollow fibers in Examples 1, 7, and 8.
[0051] Figure 13 The diagram shows the burst pressure test results of hollow fibers in Example 1, Comparative Example 7, and Comparative Example 8.
[0052] Figure 14 The diagram shows the continuous operation flux of the diffusion dialysis membrane modules in Examples 1, 5, and 9.
[0053] Figure 15 The graph shows the correlation between nitric acid recovery rate and total metal ion removal rate for Examples 1, 1, and 6.
[0054] Figure 16 The images show a comparison of the scanning electron microscope (SEM) morphology of the final product of Example 1 and the final product of Comparative Example 8; where a is a low-magnification SEM image of the final product of Example 1; b is a low-magnification SEM image of the final product of Comparative Example 8; c is a medium-magnification SEM image of the final product of Example 1; d is a medium-magnification SEM image of the final product of Comparative Example 8; e is a high-magnification SEM image of the final product of Example 1; and f is a high-magnification SEM image of the final product of Comparative Example 8. Figure 16 The quantitative results of the mesoporous structure were based on the average pore size determined by nitrogen adsorption-desorption method, and scanning electron microscope images were used to characterize the morphology and pore distribution of the hollow fibers.
[0055] Figure 17 The images show a comparison of the transmission electron microscope (TEM) structures of the final product of Example 1 and the final product of Comparative Example 8; where a is a bright-field TEM image of the final product of Example 1; b is a bright-field TEM image of the final product of Comparative Example 8; c is a high-resolution TEM image of the final product of Example 1; d is a high-resolution TEM image of the final product of Comparative Example 8; e is a selected area electron diffraction (SID) image of the final product of Example 1; and f is a SID image of the final product of Comparative Example 8. Detailed Implementation
[0056] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0057] Example 1 Sample preparation scale and waste nitric acid solution status: In this embodiment, 10 kg of waste nitric acid solution was treated using a primary diffusion dialysis unit with an effective membrane area of 0.1 m². The waste nitric acid solution originated from a metal surface treatment process, with a nitric acid mass fraction of 5 wt% and a total metal ion mass fraction of 0.05 wt% (based on metal elements), including ferrous ions and chromium ions. Before entering the diffusion dialysis membrane module, the waste nitric acid solution was pre-filtered using a filter cartridge with a 1 μm filtration precision. After filtration, the solution was allowed to stand at 25°C for 30 min, and after observing the absence of visible suspended matter, it proceeded to the treatment step.
[0058] Preparation of polybenzimidazole resin: 100 parts by weight of 3,3′-diaminobenzidine, 90 parts by weight of isophthalic acid, and 600 parts by weight of polyphosphoric acid were weighed and added to a reactor equipped with mechanical stirring and industrial nitrogen protection (purity ≥99.9%). The reactor was maintained at atmospheric pressure with a slight positive pressure. The mixture was first stirred at 80℃ for 30 min to homogenize the materials, then the temperature was increased to 180℃ at a rate of 3℃ / min, and the reaction was carried out at 180℃ for 6 h for polycondensation, with a stirring speed of 180 rpm. After the reaction, the reaction product was slowly poured into deionized water to precipitate polybenzimidazole. The product was washed with deionized water until the pH of the washing solution reached 6, and then dried at 80℃ under a vacuum degree not exceeding -0.08 MPa for 8 h to obtain polybenzimidazole resin with an intrinsic viscosity of 1.0 dL / g.
[0059] Hollow fiber forming and crosslinking: Polybenzimidazole resin was added to N,N-dimethylacetamide to prepare a spinning solution with a polybenzimidazole mass fraction of 15 wt%. The solution was mechanically stirred at 25°C for 4 hours at 300 rpm, followed by static degassing for 1 hour. During dry-jet wet spinning, the spinning solution entered the annular channel of the coaxial spinneret, and deionized water was used as the core solution. The spinning pressure was 0.05 MPa, the air gap was 5 cm, and the coagulation bath was 15°C deionized water. The coagulated polybenzimidazole hollow fibers were collected at a traction speed of 3 m / min. The polybenzimidazole hollow fibers were washed in deionized water for 24 hours, with 6 water changes, leaving 1.0 wt% residual N,N-dimethylacetamide. Washed polybenzimidazole hollow fibers were impregnated in an N,N-dimethylacetamide solution containing 1,4-di(bromomethyl)benzene. The molar ratio of 1,4-di(bromomethyl)benzene to benzimidazole NH in the polybenzimidazole hollow fibers before the reaction was 0.02:1. The reaction was carried out at 60°C for 1 h under industrial nitrogen protection. The fibers were then washed and dried at 40°C under a vacuum degree not exceeding -0.08 MPa for 4 h to obtain cross-linked polybenzimidazole hollow fibers.
[0060] Imidazole ondenylation treatment and membrane module assembly: Crosslinked polybenzimidazole hollow fibers were impregnated in an N,N-dimethylacetamide solution containing 1,4-dibromobutane, with a molar ratio of 1,4-dibromobutane to benzimidazole NH in the unreacted crosslinked polybenzimidazole hollow fibers of 0.05:1. The reaction was carried out at 50°C for 1 h under industrial nitrogen protection to introduce bromobutyl groups. The treated hollow fibers were then transferred to an N,N-dimethylacetamide solution containing 1-methylimidazole, with a molar ratio of 1-methylimidazole to the introduced bromobutyl groups of 1.0:1. The reaction was carried out at 40°C for 2 h to quaternize the fibers. The hollow fibers were washed until the bromide ion concentration in the washing solution reached 50 mg / L, and then dried at 40°C under a vacuum degree not exceeding -0.08 MPa for 4 h to obtain imidazole ondenylated crosslinked polybenzimidazole hollow fibers. Multiple hollow fibers were packed into a membrane shell to form a hollow fiber membrane bundle with a packing density of 20%.
[0061] Diffusion dialysis treatment: Waste nitric acid feed solution is fed into the feed side of the diffusion dialysis membrane module, while tap water is fed into the dialysis side. The mass flow ratio of tap water to waste nitric acid feed solution is 1:1. The feed side and dialysis side operate in a countercurrent manner. The treatment temperature is 20℃, the linear velocity on the feed side is 0.20 m / s, and the absolute value of the pressure difference between the dialysis side and the feed side is 0.01 MPa. After continuous operation for 12 hours, regeneration is performed by flushing with 20℃ tap water for 10 minutes. After treatment, the recovered acid solution and metal-rich residue are collected separately.
[0062] Quality testing methods and results: The mass fraction of nitric acid in waste nitric acid solution and recovered acid solution was determined by acid-base titration. The mass concentrations of Fe and Cr were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES), and the total metal ion content was calculated by summing the results. The content of imidazolium groups was determined by silver nitrate titration after ion exchange. The hollow fiber has an inner diameter of 300 μm, a wall thickness of 100 μm, an imidazolium group content of 0.30 mmol / g, a water content of 7.4 wt%, an average pore size of 3 nm, a porosity of 15%, a water absorption rate of 8.0 wt%, a burst pressure of 1.20 MPa, and an imidazolium-encapsulated region thickness of 20 nm. The nitric acid recovery rate was 70%, the total metal ion removal rate was 60%, and the flux decay rate was 18% after 100 hours of continuous operation.
[0063] Features and application scenarios of this embodiment: This embodiment adopts a relatively conservative low-ratio scheme and mild operating conditions. The hollow fiber size is small and the membrane bundle packing density is low. It is suitable for small-scale treatment and process start-up of waste nitric acid liquid with low acid and low metal content. It is conducive to demonstrating the feasibility and basic recovery capacity under mild conditions.
[0064] Example 2 Raw materials and proportions: This embodiment uses waste nitric acid solution generated during the stainless steel pickling process as the treatment target, with a processing volume of 50 kg. The waste nitric acid solution contains 45 wt% nitric acid and 15 wt% total metal ions (based on metal elements), including ferric, chromium, and nickel ions. The waste nitric acid solution is pre-filtered with a 100 μm filtration precision filter before entering the membrane module. The diffusion dialysis membrane module has an effective membrane area of 20.0 m², a membrane packing density of 60%, a hollow fiber inner diameter of 700 μm, and a wall thickness of 220 μm.
[0065] Resin preparation process: 100 parts by weight of 3,3′-diaminobenzidine, 110 parts by weight of isophthalic acid, and 1200 parts by weight of polyphosphoric acid were added to an industrial nitrogen-protected reactor with a nitrogen purity ≥99.9%. The mixture was stirred at 220 rpm and heated to 220°C at a rate of 2°C / min, and reacted at 220°C for 14 hours to induce polycondensation. After the reaction, the reaction product was poured into deionized water to precipitate polybenzimidazole. The product was repeatedly washed with deionized water until the pH of the washing solution reached 7, and then dried at 120°C under a vacuum not exceeding -0.08 MPa for 24 hours to obtain a polybenzimidazole resin with an intrinsic viscosity of 2.5 dL / g.
[0066] Spinning and crosslinking process: Polybenzimidazole resin was dissolved in N,N-dimethylacetamide to prepare a spinning solution with a polybenzimidazole mass fraction of 22 wt%. The solution was stirred at 35°C for 6 h at a stirring speed of 400 rpm, followed by degassing for 8 h. Dry-jet wet spinning was performed using deionized water as the core solution. The spinning pressure was 0.30 MPa, the air gap was 25 cm, the coagulation bath was 35°C deionized water, and the traction speed was 5 m / min. The resulting polybenzimidazole hollow fibers were washed with deionized water for 36 h with 8 water changes, leaving 0.8 wt% residual N,N-dimethylacetamide. Hollow fibers were impregnated in a solution of N,N-dimethylacetamide containing 1,4-di(bromomethyl)benzene. The molar ratio of 1,4-di(bromomethyl)benzene to benzimidazole NH in the unreacted polybenzimidazole hollow fibers was 0.20:1. The reaction was carried out at 90°C for 6 hours under industrial nitrogen protection. The fibers were then washed and dried at 80°C under a vacuum of no more than -0.08 MPa for 24 hours to obtain cross-linked polybenzimidazole hollow fibers.
[0067] Imidazole intumination and component operation: Crosslinked polybenzimidazole hollow fibers were impregnated in an N,N-dimethylacetamide solution containing 1,4-dibromobutane, with a molar ratio of 1,4-dibromobutane to benzimidazole NH in the unreacted crosslinked polybenzimidazole hollow fibers of 0.50:1. The reaction was carried out at 90°C for 8 h under industrial nitrogen protection. The treated hollow fibers were then transferred to an N,N-dimethylacetamide solution containing 1-methylimidazole, with a molar ratio of 1-methylimidazole to introduced bromobutyl groups of 3.0:1. The reaction was carried out at 80°C for 12 h for quaternization. The hollow fibers were washed until the bromide ion concentration in the washing solution reached 40 mg / L, and then dried at 80°C under a vacuum degree not exceeding -0.08 MPa for 24 h to obtain imidazole intuminated crosslinked polybenzimidazole hollow fibers. During diffusion dialysis operation, the mass flow ratio of tap water to waste nitric acid feed solution was 6:1, the treatment temperature was 45℃, the feed solution linear velocity was 1.00 m / s, and the absolute value of the pressure difference between the dialysis side and the feed solution side was 0.15 MPa. Mass transfer between the feed solution side and the dialysis side was carried out in a countercurrent manner. After continuous operation for 72 hours, regeneration was performed by flushing with 40℃ tap water for 60 minutes.
[0068] Quality testing methods and results: The mass fraction of nitric acid was determined by acid-base titration; the mass concentrations of Fe, Cr, and Ni were determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) and the total metal ion content was calculated; the imidazolium group content was determined by ion exchange followed by ion chromatography; the average pore size was determined by nitrogen adsorption-desorption, and the porosity was determined by impregnation-weighing method. The hollow fiber imidazolium group content was 1.20 mmol / g, the water content was 16.7 wt%, the average pore size was 25 nm, the porosity was 45%, the water absorption rate was 20.0 wt%, the burst pressure was 0.20 MPa, and the thickness of the imidazolium-encapsulated region was 120 nm. The nitric acid recovery rate was 95%, the total metal ion removal rate was 95%, and the flux decay rate was 20% after 500 hours of continuous operation.
[0069] The process features and application directions of this embodiment: This embodiment adopts a high load ratio and operating conditions, with a high membrane module area and packing density, which is suitable for the continuous treatment of waste nitric acid solution from stainless steel pickling with high acid and high metal content. It can demonstrate the coordinated ability of acid recovery and metal ion retention under enhanced operating conditions.
[0070] Example 3 In this embodiment, the waste nitric acid solution originates from the post-nitration washing process, with a processing capacity of 25 kg. The nitric acid mass fraction is 20 wt%, and the total metal ion mass fraction (based on metal elements) is 5 wt%, including divalent copper ions, divalent zinc ions, and trivalent iron ions. After pre-filtration with a 50 μm filtration precision, the waste nitric acid solution enters the diffusion dialysis membrane module. The effective membrane area of the diffusion dialysis membrane module is 5.0 m², and the membrane bundle packing density is 40%.
[0071] Polybenzimidazole resin was prepared as follows: 100 parts by weight of 3,3′-diaminobenzidine, 100 parts by weight of isophthalic acid, and 900 parts by weight of polyphosphoric acid were added to a reactor. The mixture was stirred at 200 rpm under industrial nitrogen protection, first at 100°C for 40 min, then heated to 200°C at a rate of 2.5°C / min and reacted for 10 h. The reaction product was poured into deionized water to precipitate polybenzimidazole. The product was washed until the pH of the washing solution reached 6.5, and then dried at 100°C under a vacuum not exceeding -0.08 MPa for 16 h to obtain polybenzimidazole resin with an intrinsic viscosity of 1.8 dL / g.
[0072] Polybenzimidazole resin was dissolved in N,N-dimethylacetamide to prepare a spinning solution with a polybenzimidazole mass fraction of 18 wt%. The solution was stirred at 25°C for 5 h and then degassed for 4 h. Dry-jet wet spinning conditions were: deionized water core solution, spinning pressure 0.18 MPa, air gap 15 cm, coagulation bath at 25°C with deionized water, and traction speed 4 m / min. After washing the polybenzimidazole hollow fibers for 30 h, the residual N,N-dimethylacetamide was 0.6 wt%. The washed hollow fibers were then impregnated in an N,N-dimethylacetamide solution containing 1,4-di(bromomethyl)benzene. The molar ratio of 1,4-di(bromomethyl)benzene to benzimidazole NH in the unreacted polybenzimidazole hollow fibers was 0.10:1. The reaction was carried out at 75°C for 3 h under industrial nitrogen protection. After washing, the fibers were dried at 60°C under a vacuum degree not exceeding -0.08 MPa for 12 h to obtain cross-linked polybenzimidazole hollow fibers.
[0073] During bromobutylation, cross-linked polybenzimidazole hollow fibers were impregnated in an N,N-dimethylacetamide solution containing 1,4-dibromobutane. The molar ratio of 1,4-dibromobutane to benzimidazole NH in the unreacted cross-linked polybenzimidazole hollow fibers was 0.25:1. The reaction was carried out at 70°C for 4 hours under industrial nitrogen protection. During quaternization, the treated hollow fibers were transferred to an N,N-dimethylacetamide solution containing 1-methylimidazole. The molar ratio of 1-methylimidazole to the introduced bromobutyl group was 2.0:1. The reaction was carried out at 60°C for 6 hours. The hollow fibers were washed until the bromide ion concentration in the washing solution reached 30 mg / L, and then dried at 60°C under a vacuum not exceeding -0.08 MPa for 12 hours to obtain imidazole-onthiolated cross-linked polybenzimidazole hollow fibers.
[0074] During diffusion dialysis operation, the mass flow ratio of tap water to waste nitric acid feed solution was 3:1, the treatment temperature was 30℃, the feed solution linear velocity was 0.60 m / s, and the absolute value of the pressure difference between the dialysis side and the feed solution side was 0.08 MPa. Countercurrent mass transfer was employed. After 48 hours of continuous operation, regeneration was performed by flushing with 30℃ tap water for 30 minutes. The recovered acid solution and metal-rich residual solution were collected separately.
[0075] Quality testing methods and results: The mass fraction of nitric acid was determined by acid-base titration; the mass concentrations of Cu, Zn, and Fe were determined by inductively coupled plasma mass spectrometry (ICP-MS) and the total metal ion content was calculated; and the imidazolium group content was determined by silver nitrate titration. The hollow fiber had an inner diameter of 500 μm, a wall thickness of 160 μm, an imidazolium group content of 0.75 mmol / g, a water content of 12.3 wt%, an average pore size of 12 nm, a porosity of 30%, a water absorption rate of 14.0 wt%, a burst pressure of 0.70 MPa, and an imidazolium-encapsulated region thickness of 70 nm. The nitric acid recovery rate was 86%, the total metal ion removal rate was 88%, and the flux decay rate was 10% after 300 hours of continuous operation.
[0076] The features of this embodiment are: This embodiment adopts a medium ratio and medium operating conditions. The waste nitric acid feed comes from the washing process after nitration. The hollow fiber membrane structure is in a relatively balanced state. It is suitable for continuous treatment scenarios with small composition fluctuations but need to take into account the quality of recovered acid and operational stability.
[0077] Example 4 I. Treatment Object and Membrane Module Status: The treatment object is waste nitric acid solution generated during the electronic chemical cleaning process, with a processing capacity of 30 kg. The waste nitric acid solution contains 35 wt% nitric acid and 10 wt% total metal ions (based on metal elements), including trivalent aluminum ions, divalent manganese ions, and titanium-containing metal ions. The waste nitric acid solution is pre-filtered with a 20 μm filtration precision before entering the diffusion dialysis membrane module. The effective membrane area of the diffusion dialysis membrane module is 12.0 m², and the membrane packing density is 50%.
[0078] II. Preparation of polybenzimidazole resin: 100 parts by weight of 3,3′-diaminobenzidine, 105 parts by weight of isophthalic acid, and 1000 parts by weight of polyphosphoric acid were added to a reactor and stirred at 210 rpm under industrial nitrogen protection. The system was heated to 210℃ at 2℃ / min and reacted for 12 h for polycondensation. The reaction product was poured into deionized water to precipitate polybenzimidazole. The product was washed until the pH of the washing solution reached 6.8, and then dried at 110℃ under a vacuum degree not exceeding -0.08 MPa for 20 h to obtain polybenzimidazole resin with an intrinsic viscosity of 2.1 dL / g.
[0079] III. Hollow Fiber Preparation and Crosslinking Treatment: Polybenzimidazole resin was dissolved in N,N-dimethylacetamide to prepare a spinning solution with a polybenzimidazole content of 20 wt%, and defoamed at 30°C for 6 h. Dry-jet wet spinning was performed using deionized water as the core solution, with a spinning pressure of 0.25 MPa, an air gap of 20 cm, a coagulation bath of 30°C deionized water, and a traction speed of 5 m / min. After washing the polybenzimidazole hollow fibers for 32 h, the residual N,N-dimethylacetamide content was 0.5 wt%. The washed hollow fibers were impregnated in an N,N-dimethylacetamide solution containing 1,4-di(bromomethyl)benzene. The molar ratio of 1,4-di(bromomethyl)benzene to benzimidazole NH in the polybenzimidazole hollow fibers before the reaction was 0.15:1. The reaction was carried out at 85°C for 5 hours under industrial nitrogen protection. The fibers were then washed and dried at 70°C under a vacuum of no more than -0.08 MPa for 18 hours to obtain cross-linked polybenzimidazole hollow fibers.
[0080] IV. Imidazole Intumization and Post-treatment: Crosslinked polybenzimidazole hollow fibers were impregnated in an N,N-dimethylacetamide solution containing 1,4-dibromobutane, with a molar ratio of 1,4-dibromobutane to benzimidazole NH in the unreacted crosslinked polybenzimidazole hollow fibers of 0.40:1. The reaction was carried out at 80°C for 6 hours under industrial nitrogen protection. The treated hollow fibers were then transferred to an N,N-dimethylacetamide solution containing 1-methylimidazole, with a molar ratio of 1-methylimidazole to introduced bromobutyl groups of 2.5:1. The reaction was carried out at 70°C for 10 hours to quaternize the fibers. After washing until the bromide ion concentration in the washing solution reached 20 mg / L, the fibers were dried at 70°C under a vacuum degree not exceeding -0.08 MPa for 18 hours to obtain imidazole intumized crosslinked polybenzimidazole hollow fibers.
[0081] V. Diffusion Dialysis Treatment and Regeneration: Waste nitric acid solution was fed into the feed side, and tap water was fed into the dialysis side. The mass flow ratio of tap water to waste nitric acid solution was 4:1. The treatment temperature was 38℃, the linear velocity on the feed side was 0.80 m / s, and the absolute value of the pressure difference between the dialysis and feed sides was 0.12 MPa. The feed and dialysis sides operated in a countercurrent manner. After 60 hours of continuous operation, regeneration was performed by flushing with 35℃ tap water for 45 minutes. The recovered acid and metal-rich residue were collected separately after treatment.
[0082] VI. Quality Testing Methods and Results: The mass fraction of nitric acid was determined by acid-base titration. The mass concentration of actual metal elements in Al, Mn, and Ti was determined by inductively coupled plasma mass spectrometry (ICP-MS) and the total metal ion content was calculated. The imidazolium group content was determined by ion exchange followed by ion chromatography. The distribution of N and Br elements along the wall thickness was recorded by transmission electron microscopy (TEM) energy dispersive spectroscopy. The hollow fiber had an inner diameter of 620 μm, a wall thickness of 200 μm, an imidazolium group content of 1.00 mmol / g, a water content of 14.5 wt%, an average pore size of 18 nm, a porosity of 38%, a water absorption rate of 17.0 wt%, a burst pressure of 0.45 MPa, and an imidazolium-treated region thickness of 95 nm. The nitric acid recovery rate was 90%, the total metal ion removal rate was 91%, and the flux decay rate was 12% after 400 hours of continuous operation.
[0083] Comparative Example 1: Basically the same as Example 1, except that the content of imidazole onion groups in the hollow fiber was adjusted to 0.20 mmol / g, the mass fraction of nitric acid in the waste nitric acid feed was maintained at 5 wt%, the mass fraction of total metal ions (calculated as metal elements) was maintained at 0.05 wt%, the treatment temperature was maintained at 20℃, the linear velocity of the feed side was maintained at 0.20 m / s, the absolute value of the pressure difference between the dialysis side and the feed side was maintained at 0.01 MPa, the mass flow ratio of tap water to waste nitric acid feed was maintained at 1:1, the filtration accuracy was maintained at 1 μm, the effective membrane area of the diffusion dialysis membrane module was maintained at 0.1 m², and the membrane bundle packing density was maintained at 20%.
[0084] Comparative Example 2: Basically the same as Example 1, except that the content of imidazole onion groups in the hollow fiber was adjusted to 1.50 mmol / g, the mass fraction of nitric acid in the waste nitric acid feed was maintained at 5 wt%, the mass fraction of total metal ions (calculated as metal elements) was maintained at 0.05 wt%, the treatment temperature was maintained at 20℃, the feed side linear velocity was maintained at 0.20 m / s, the absolute value of the pressure difference between the dialysis side and the feed side was maintained at 0.01 MPa, the mass flow ratio of tap water to waste nitric acid feed was maintained at 1:1, the filtration accuracy was maintained at 1 μm, the effective membrane area of the diffusion dialysis membrane module was maintained at 0.1 m², and the membrane bundle packing density was maintained at 20%.
[0085] Comparative Example 3: Basically the same as Example 1, except that the treatment temperature was adjusted to 15°C, the mass fraction of nitric acid in the waste nitric acid feed was maintained at 5 wt%, the mass fraction of total metal ions (based on metal elements) was maintained at 0.05 wt%, the content of imidazolium groups in hollow fibers was maintained at 0.30 mmol / g, the linear velocity of the feed side was maintained at 0.20 m / s, the absolute value of the pressure difference between the dialysis side and the feed side was maintained at 0.01 MPa, the mass flow ratio of tap water to waste nitric acid feed was maintained at 1:1, the filtration accuracy was maintained at 1 μm, the effective membrane area of the diffusion dialysis membrane module was maintained at 0.1 m², and the membrane packing density was maintained at 20%.
[0086] Comparative Example 4: Basically the same as Example 1, except that the linear velocity of the feed liquid was adjusted to 0.10 m / s, the mass fraction of nitric acid in the waste nitric acid feed liquid was maintained at 5 wt%, the mass fraction of total metal ions (based on metal elements) was maintained at 0.05 wt%, the content of imidazolium groups in hollow fibers was maintained at 0.30 mmol / g, the treatment temperature was maintained at 20℃, the absolute value of the pressure difference between the dialysis side and the feed liquid side was maintained at 0.01 MPa, the mass flow ratio of tap water to waste nitric acid feed liquid was maintained at 1:1, the filtration accuracy was maintained at 1 μm, the effective membrane area of the diffusion dialysis membrane module was maintained at 0.1 m², and the membrane bundle packing density was maintained at 20%.
[0087] Comparative Example 5: Basically the same as Example 1, except that the absolute value of the pressure difference between the dialysis side and the feed side was adjusted to 0.20 MPa, the mass fraction of nitric acid in the waste nitric acid feed was maintained at 5 wt%, the mass fraction of total metal ions (based on metal elements) was maintained at 0.05 wt%, the content of imidazolium groups in hollow fibers was maintained at 0.30 mmol / g, the treatment temperature was maintained at 20 °C, the linear velocity on the feed side was maintained at 0.20 m / s, the mass flow ratio of tap water to waste nitric acid feed was maintained at 1:1, the filtration accuracy was maintained at 1 μm, the effective membrane area of the diffusion dialysis membrane module was maintained at 0.1 m², and the membrane bundle packing density was maintained at 20%.
[0088] Comparative Example 6: Basically the same as Example 1, except that the mass flow ratio of tap water to waste nitric acid feed was adjusted to 0.5:1, the mass fraction of nitric acid in the waste nitric acid feed was maintained at 5 wt%, the mass fraction of total metal ions (based on metal elements) was maintained at 0.05 wt%, the content of imidazolium groups in hollow fiber was maintained at 0.30 mmol / g, the treatment temperature was maintained at 20℃, the feed side linear velocity was maintained at 0.20 m / s, the absolute value of the pressure difference between the dialysis side and the feed side was maintained at 0.01 MPa, the filtration accuracy was maintained at 1 μm, the effective membrane area of the diffusion dialysis membrane module was maintained at 0.1 m², and the membrane bundle packing density was maintained at 20%.
[0089] Comparative Example 7: Basically the same as Example 1, except that the molar ratio of 1,4-di(bromomethyl)benzene to benzimidazole NH in the pre-reaction polybenzimidazole hollow fiber was adjusted to 0.01:1, the mass fraction of nitric acid in the waste nitric acid solution was maintained at 5 wt%, the mass fraction of total metal ions (based on metal elements) was maintained at 0.05 wt%, the content of imidazole onium groups in the hollow fiber was maintained at 0.30 mmol / g, the treatment temperature was maintained at 20℃, the linear velocity of the feed solution was maintained at 0.20 m / s, the absolute value of the pressure difference between the dialysis side and the feed solution side was maintained at 0.01 MPa, the mass flow ratio of tap water to waste nitric acid solution was maintained at 1:1, and the filtration accuracy was maintained at 1 μm.
[0090] Comparative Example 8: Basically the same as Example 1, except that the mass fraction of polybenzimidazole in the polybenzimidazole spinning solution in the hollow fiber forming and crosslinking steps was adjusted from 15wt% to 10wt%, resulting in hollow fibers with an average pore size of 40nm. The mass fraction of nitric acid in the waste nitric acid solution was maintained at 5wt%, the mass fraction of total metal ions (based on metal elements) was maintained at 0.05wt%, the content of imidazole ontium groups in the hollow fiber was maintained at 0.30mmol / g, the treatment temperature was maintained at 20℃, the linear velocity of the feed solution was maintained at 0.20m / s, the absolute value of the pressure difference between the dialysis side and the feed solution side was maintained at 0.01MPa, the mass flow ratio of tap water to waste nitric acid solution was maintained at 1:1, and the filtration accuracy was maintained at 1μm.
[0091] Comparative Example 9: Essentially the same as Example 1, except that the 1,4-di(bromomethyl)benzene crosslinking step was omitted. The polybenzimidazole hollow fibers were directly subjected to 1,4-dibromobutane bromobutylation and 1-methylimidazolium quaternization after washing. The nitric acid mass fraction in the waste nitric acid solution was maintained at 5 wt%, the total metal ion mass fraction (based on metal elements) was maintained at 0.05 wt%, the treatment temperature was maintained at 20°C, the feed liquid side linear velocity was maintained at 0.20 m / s, the absolute value of the pressure difference between the dialysis side and the feed liquid side was maintained at 0.01 MPa, the mass flow ratio of tap water to waste nitric acid solution was maintained at 1:1, and the filtration accuracy was maintained at 1 μm. This comparative example was used to investigate the synergistic relationship between the crosslinked polybenzimidazole matrix and the imidazolium-encapsulated region.
[0092] Comparative Example 10: Essentially the same as Example 1, except that the 1,4-di(bromomethyl)benzene crosslinking step was retained, but the 1,4-dibromobutane bromobutylation and 1-methylimidazolium quaternization treatments were omitted. The mass fraction of nitric acid in the waste nitric acid feed solution was maintained at 5 wt%, the total metal ion mass fraction (based on metal elements) was maintained at 0.05 wt%, the treatment temperature was maintained at 20 °C, the feed solution side linear velocity was maintained at 0.20 m / s, the absolute value of the pressure difference between the dialysis side and the feed solution side was maintained at 0.01 MPa, the mass flow ratio of tap water to waste nitric acid feed solution was maintained at 1:1, and the filtration accuracy was maintained at 1 μm. This comparative example was used to investigate the synergistic relationship between the crosslinked polybenzimidazole matrix and the imidazolium-enhanced region.
[0093] Comparative Example 11: Essentially the same as Example 1, except that the order of bromobutylation followed by quaternization in Example 1 was adjusted. Instead, cross-linked polybenzimidazole hollow fibers were first impregnated in an N,N-dimethylacetamide solution containing 1-methylimidazole and treated at 40°C for 2 hours, then transferred to an N,N-dimethylacetamide solution containing 1,4-dibromobutane and treated at 50°C for 1 hour. The mass fraction of nitric acid in the waste nitric acid feed solution was maintained at 5 wt%, the total metal ion mass fraction (based on metal elements) was maintained at 0.05 wt%, the treatment temperature was maintained at 20°C, the feed solution linear velocity was maintained at 0.20 m / s, the absolute value of the pressure difference between the dialysis side and the feed solution side was maintained at 0.01 MPa, the mass flow ratio of tap water to waste nitric acid feed solution was maintained at 1:1, and the filtration accuracy was maintained at 1 μm. This comparative example was used to investigate the effect of the bromobutylation and quaternization order on the synergistic relationship.
[0094] Performance testing: The experiment on nitric acid content and recovery rate used waste nitric acid feed solution, recovered acid solution, and metal-rich residue as test objects to evaluate the recovery level of nitric acid after its migration from the feed solution side to the dialysis side. The weighed samples were diluted to a fixed volume, and the total acidity was determined by acid-base titration with sodium hydroxide standard solution. The nitrate content was determined by ion chromatography to eliminate interference from non-nitric acidity. When inorganic anions were involved, ion chromatography was performed according to HJ84-2016 "Determination of Inorganic Anions in Water Quality - Ion Chromatography Method," a standard publicly released by the Ministry of Ecology and Environment. Data were calculated with n=3 for mean and standard deviation. The recorded fields were nitric acid mass fraction and nitric acid recovery rate, in units of wt% and %, respectively. Higher values indicate higher recovery levels.
[0095] The experiments on total metal ion content and total metal ion removal rate used waste nitric acid solution, recovered acid solution, and metal-rich residual solution as test objects. The purpose was to evaluate the residual levels of the actual metal elements (Fe, Cr, Ni, Al, Cu, Zn, Mn, and Ti) in the recovered acid solution. After volumetric dilution and necessary digestion, the mass concentration of each metal element was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES) or inductively coupled plasma mass spectrometry (ICP-MS), and the total metal ion content was calculated by summation. For water samples, multi-element ICP-OES can refer to HJ776-2015, and ICP-MS can refer to HJ700-2014. The data fields are the total metal ion content and total metal ion removal rate of the recovered acid solution, in g / L and %, respectively. Lower metal content and higher removal rate indicate better separation effect. When calculating the total metal ion removal rate, the corresponding mass or volume of waste nitric acid solution and recovered acid solution were recorded, and the total metal ion mass in the corresponding sample was converted according to the measured total metal ion mass concentration.
[0096] The diffusion dialysis flux and flux decay rate experiment used the assembled diffusion dialysis membrane module as the test object to evaluate its continuous operation stability. Waste nitric acid feed and tap water of the same composition were introduced into the feed side and dialysis side, respectively. Under set conditions of treatment temperature, feed side linear velocity, absolute value of pressure difference between the dialysis side and feed side, and mass flow rate ratio, the volume of acid recovered per unit time was recorded, or the mass of recovered acid was recorded and converted to volume according to its density. The initial flux was calculated based on the effective membrane area. After continuous operation for the set time, the flux was measured again under the same conditions. The flux decay rate was calculated by dividing the difference between the initial flux and the flux after continuous operation by the initial flux. The data fields are initial flux, flux after continuous operation, and flux decay rate, in L·m. -2 ·h -1 The lower the flux decay rate, the better the operational stability.
[0097] The imidazolium group content and imidazolium-encapsulated region thickness experiments used imidazolium-encapsulated cross-linked polybenzimidazole hollow fibers as the test object to evaluate the content of ion sites and their distribution in the membrane wall. Dry hollow fibers were subjected to ion exchange treatment to allow exchangeable anions to enter the exchange solution. The amount of anions was determined by silver nitrate titration or ion chromatography, and the imidazolium group content was calculated based on the dry mass of the sample. Cross-sectional samples were analyzed using transmission electron microscopy line scanning or X-ray photoelectron spectroscopy depth profiling to record the distribution of N and Br elements. Data fields include imidazolium group content and imidazolium-encapsulated region thickness, in mmol / g and nm, respectively. The results are used to illustrate the level of structural regulation.
[0098] Hollow fiber pore structure, water content, and burst pressure experiments were conducted using dry and wet hollow fibers to evaluate mass transfer channels and structural integrity. Inner diameter and wall thickness were statistically analyzed using optical microscopy or scanning electron microscopy. Pore size distribution and average pore size were calculated using nitrogen adsorption-desorption. Water content and water absorption were calculated by weighing after immersion in deionized water at 25°C for 24 hours. Porosity was calculated using the ratio of pore volume to apparent volume of the hollow fiber. A single hollow fiber was sealed at both ends, and water or nitrogen was continuously introduced into the cavity with increasing pressure; the burst pressure was recorded as the burst pressure. Data fields included inner diameter, wall thickness, average pore size, porosity, water content, water absorption, and burst pressure, in units of μm, nm, %, wt%, and MPa.
[0099] The residual N,N-dimethylacetamide and polybenzimidazole intrinsic viscosity experiments used washed polybenzimidazole hollow fibers and polybenzimidazole resin as test objects to evaluate the quality related to solvent residue and resin molecular weight after spinning. Hollow fiber samples were extracted with deionized water, and the N,N-dimethylacetamide content of the extract was determined by gas chromatography or high-performance liquid chromatography. The residual amount was calculated based on the ratio of the extracted solvent mass to the sample mass. Polybenzimidazole resin was dissolved in N,N-dimethylacetamide to form a test solution. The elution time was measured using an Ubbelohde viscometer at 25°C, and the intrinsic viscosity was calculated using the dilution extrapolation method. Data fields are residual N,N-dimethylacetamide content and intrinsic viscosity, in wt% and dL / g, respectively.
[0100] Figure 1 The graph shows the effect of imidazolium group content on nitric acid recovery and total metal ion removal rate. Figure 2 The graph shows the effect of the water-to-material mass flow rate ratio on nitric acid recovery rate and total metal ion removal rate. Figure 3 The graph shows the effect of temperature on nitric acid recovery and total metal ion removal rate. Figure 4 The graph shows the effect of the crosslinking agent molar ratio on nitric acid recovery and total metal ion removal rate. Figures 1 to 4 First, the matching relationship between nitric acid recovery and metal ion retention was verified from two aspects: functionalization level and operating conditions. Specifically, Figure 1 Based on the membrane preparation and diffusion dialysis conditions of Example 1, only the imidazolium group content was varied, ranging from approximately 0.20 to 1.50 mmol / g. When the imidazolium group content was low, there were insufficient exchange sites within the membrane to participate in anion transport, limiting nitrate migration. Conversely, when the imidazolium group content was too high, the hydrophilicity and chain segment constraint of the membrane changed, increasing mass transfer resistance and swelling risk, leading to decreased separation selectivity. Therefore, a moderate imidazolium group content can provide continuous transport sites for nitrate while avoiding excessive ionization that weakens membrane structural stability. Figure 2Based on Example 1, only the mass flow rate ratio of tap water to waste nitric acid solution was changed, with a variable range of approximately 0.5-7.0. When the water-to-solid mass flow rate ratio was too low, the driving force for nitric acid diffusion was insufficient, resulting in low recovery efficiency. When the water-to-solid mass flow rate ratio was too high, although the driving force for mass transfer increased, the degree of system dilution increased, and the unit treatment efficiency and ion selectivity were affected. Figure 3 Based on Example 1, only the processing temperature was changed, with a range of approximately 15-50°C. Moderate heating is beneficial to increase the nitrate diffusion rate, but excessively high temperatures will exacerbate membrane swelling and non-selective ion migration. Figure 4 Based on Example 1, only the molar ratio of the 1,4-bis(bromomethyl)benzene crosslinking agent was changed, with a range of approximately 0.01-0.25. When the amount of crosslinking agent was insufficient, the membrane wall structure was not sufficiently constrained, and the metal ion retention capacity decreased. When the amount of crosslinking agent was too high, the mass transfer channels were excessively contracted, and the nitric acid migration efficiency decreased. Therefore, Figures 1 to 4 This demonstrates that the imidazolium group content, water-to-material mass flow ratio, treatment temperature, and crosslinking agent molar ratio are not isolated parameters, but rather key factors that collectively determine acid mass transfer, metal ion barrier, and membrane stability. Example 1 achieved a simultaneous improvement in nitric acid recovery efficiency and metal ion removal effect through the synergistic matching of the above parameters.
[0101] Figure 5 The graph shows the determination of imidazolium group content. Figure 6 This is a distribution diagram of Br element along the wall thickness direction of the hollow fiber. Figure 7 This is a distribution diagram of nitrogen (N) along the wall thickness of the hollow fiber. For further explanation... Figures 1 to 4 The performance improvement stems from the membrane structure itself, rather than simply from changes in operating conditions. Figures 5 to 7 The functionalization level and elemental spatial distribution of Example 1 and related comparative examples were verified. Figure 5 The imidazolium group content of Example 1, Comparative Example 9, and Comparative Example 10 was compared using repeated test scatter plots and mean ± standard deviation. The results showed that Example 1 had a more stable and moderate imidazolium group content, while the functionalization degree of Comparative Example 10 was significantly insufficient, indicating that Example 1 can effectively introduce ion exchange sites involved in nitrate transfer. Figure 6 The distribution of crosslinking and quaternization-related structures along the thickness direction of the hollow fiber was reflected by Br element line scanning. In Example 1, there was a significant Br element signal near the outer surface, which gradually decreased along the thickness direction, indicating that the functionalized regions were mainly formed near the effective mass transfer interface of the hollow fiber, rather than indiscriminately penetrating the entire membrane wall. Figure 7The relative enhancement of nitrogen distribution caused by imidazole ondenylation treatment was further verified by nitrogen element line scanning. In Example 1, the nitrogen element signal on the surface was enhanced and continuous, while the change was weaker in Comparative Example 10, indicating that the nitrogen-containing ion exchange structure is mainly distributed in the surface and near-surface regions. Therefore, Example 1, through surface and near-surface functionalization, provides sufficient transport sites for nitrate ions at the effective interface, while avoiding excessive functionalization that would increase the overall mass transfer resistance. This structural approach explains why it can balance nitrate recovery and membrane stability.
[0102] Figure 8 This is a differential pore size distribution diagram of hollow fibers. Figure 9 This is a cumulative pore size distribution diagram of hollow fibers. Figure 10 This is a graph showing the porosity of hollow fibers. Figure 11 This is a graph showing the moisture content of hollow fibers. Figure 12 This is a graph showing the water absorption rate of hollow fibers. Figure 13 This is a diagram of the burst pressure test of hollow fiber. Figures 8 to 13 Further, from three levels—pore structure, water absorption and swelling behavior, and mechanical pressure bearing capacity—it is explained that Example 1 can resolve the contradiction that "improving mass transfer performance easily weakens structural integrity, while improving structural constraints easily hinders nitric acid mass transfer." Figure 8 By comparing the pore size difference distribution curves of Example 1, Comparative Example 7 and Comparative Example 8, the pore size distribution of Example 1 is concentrated and the peak position is smaller, while the pore size of Comparative Example 8 is significantly larger and the distribution is wider. This indicates that Example 1 forms a finer pore that is more conducive to the selective migration of nitrate ions and at the same time restricts the penetration of metal ions. Figure 9 Further evidence from the cumulative pore size distribution shows that the cumulative distribution curve of Example 1 rises rapidly in the small pore size region, indicating that it has a higher proportion of small pores, a narrower pore size distribution, and a more uniform membrane pore structure. Figure 10 The porosity of Example 1 is within a moderate range, while the porosity of Comparative Example 7 is too low, which can easily lead to insufficient acid mass transfer. The porosity of Comparative Example 8 is too high, which can easily lead to a decrease in metal ion retention. Figure 11 and Figure 12 The results reflect the water content and water absorption rate, respectively. Example 1 has a low water content with small fluctuations and a moderate water absorption rate, indicating that the membrane is not prone to excessive swelling in aqueous and acidic systems, which can avoid pore enlargement and subsequent decrease in selectivity. Figure 13 Further, the burst pressure of Example 1 is higher than that of Comparative Examples 7 and 8, indicating that it maintains good hydraulic resistance while preserving nanoscale mass transfer channels. These results demonstrate that Example 1 does not improve nitric acid mass transfer simply by increasing porosity, but rather through the combined effects of moderate porosity, narrow pore size distribution, controlled water absorption behavior, and a cross-linked framework, enabling the hollow fiber to simultaneously possess usable mass transfer channels and a stable pressure-bearing structure.
[0103] Figure 14 This is a flux diagram for continuous operation of a diffusion dialysis membrane module. Figure 15This is a graph showing the correlation between nitric acid recovery rate and total metal ion removal rate. After completing the membrane material structure verification... Figure 14 and Figure 15 The practical application effect of Example 1 is further evaluated from the perspectives of component operation stability and overall separation effect. Figure 14 Plotting operating time on the x-axis, the flux changes of the diffusion dialysis membrane modules of Example 1, Comparative Example 5, and Comparative Example 9 within 0-100 hours were recorded, and the standard deviation band was used to reflect repeatability. The results showed that Example 1 exhibited a slower flux decay and smaller fluctuations during continuous operation, indicating that its functionalized regions and cross-linked matrix could maintain a stable mass transfer state under waste nitric acid conditions. In contrast, the flux decrease of the comparative example samples was more significant, indicating insufficient stability of their membrane structure or functional layers. Figure 15 The nitric acid recovery rate and total metal ion removal rate of Example 1, Comparative Example 1, and Comparative Example 6 are simultaneously displayed using two-dimensional scatter plots and bidirectional error bars. Example 1 is located in the region where both nitric acid recovery rate and metal ion removal rate are superior, while the comparative examples typically show improved acid recovery capacity but insufficient metal ion retention, or improved retention capacity but limited acid mass transfer. This demonstrates that Example 1 can maintain the structural advantages at the material level at the component scale, achieving simultaneous improvement in nitric acid recovery, metal ion removal, and operational stability.
[0104] Figure 16 The images show a comparison of the scanning electron microscope morphology of the final product. Figure 16 a to Figure 16 f is used to further illustrate the structural refinement advantage of Example 1 compared to Comparative Example 8 from a microscopic morphology perspective. Figure 16 a shows that the final product of Example 1, after undergoing crosslinking and imidazole ondenylation treatment, still maintains a hollow fiber tubular structure with an outer diameter of about 500 μm, an inner diameter of about 300 μm, and a wall thickness of about 100 μm, indicating that the multi-step chemical treatment did not damage the main morphology of the fiber. Figure 16 b shows that Comparative Example 8 also maintains a similar size, making the two geometrically comparable. Figure 16 c shows that the approximately 100 μm wall layer of Example 1 is continuous and the inner and outer surfaces are intact, indicating that the cross-linked polybenzimidazole matrix can provide stable membrane wall support; Figure 16 Figure d shows that although the wall layer size of Comparative Example 8 is maintained, the pore structure is more open, suggesting that excessively large pores will reduce the local compactness of the membrane wall. Further analysis at high magnification... Figure 16 e shows that the surface and pore wall regions of Example 1 are relatively dense; the average pore size of Example 1 is about 3 nm, which is the value determined by nitrogen adsorption-desorption method, and the thickness of the imidazole-encapsulated region is about 20 nm, indicating that Example 1 formed refined nanopore channels and functionalized pore walls; Figure 16As shown in Figure f, after the average pore size of Comparative Example 8 increased to approximately 40 nm, the openness of the pore walls significantly increased, making it difficult to maintain a fine sieving structure. Therefore, Example 1, without sacrificing the size and integrity of the hollow fiber body, effectively controlled the pore structure at the nanoscale and constructed functionalized regions near the pore walls, providing a morphological basis for rapid nitrate migration and metal ion blocking.
[0105] Figure 17 The images show a comparison of the transmission electron microscope structure of the final product. Figure 17 a to Figure 17 f Further, from the perspective of nanopore structure and functionalized region distribution, Figure 16 The morphological results were further verified. Figure 17 a shows that the local structure of the pore wall in Example 1 is dense; the average pore diameter of Example 1 is about 3 nm, which is the value determined by nitrogen adsorption-desorption method. There is an imidazole-onium region about 20 nm thick near the pore wall, indicating that it forms a continuous and refined nano-mass transfer channel. Figure 17 b shows that in Comparative Example 8, after the average pore size increased to approximately 40 nm, the local channels became more pronounced, and the sieving effect of the pore walls was relatively weakened. Figure 17 c shows that the polybenzimidazole matrix of Example 1 is mainly in an amorphous or low-order chain segment stacking state with good pore wall continuity, indicating that its performance improvement mainly comes from the synergy of nanoporous structure and functionalized regions, rather than the difference in amorphous structure. Figure 17 d shows that the local uniformity of the pore wall in Comparative Example 8 is reduced under the condition of larger pore size, indicating that pore size enlargement will weaken the stability of microstructure. Figure 17 e. Selected area electron diffraction showed that the matrix of Example 1 was mainly amorphous or low-order. Figure 17 The matrix characteristics of Comparative Example 8 are similar to those of Example 1, but there are significant differences in pore structure scale, further illustrating that the performance differences mainly stem from pore size control and the construction of functionalized regions. Combined with... Figure 16 and Figure 17 It can be confirmed that Example 1, through the synergistic design of approximately 3 nm nanopores, approximately 20 nm imidazole-encapsulated regions, and a complete hollow fiber skeleton, simultaneously satisfies the requirements of acid mass transfer, metal ion barrier, and membrane integrity in its microstructure.
[0106] In conclusion, Figures 1 to 17Following the logical progression of "key parameter optimization—functionalized structure confirmation—pore structure and mechanical stability verification—continuous component operation evaluation—microscopic morphology verification," this study demonstrates that Example 1 does not rely on improvement based on a single indicator. Instead, it achieves a mutually corrective relationship between structural constraints, nitric acid mass transfer, and metal ion retention through the matching of the cross-linked polybenzimidazole matrix, the imidazole-encapsulated region, and the countercurrent diffusion dialysis conditions. These results indicate that this approach effectively alleviates the difficulty in balancing structural integrity, nitric acid recovery, processing fluidity, and metal ion retention in diffusion dialysis membranes, achieving a comprehensive performance improvement in the waste nitric acid treatment and recovery process.
[0107] Table 1 Performance summary of examples and comparative examples
[0108] As can be seen from the performance of the examples and comparative examples in the table, Examples 1–4 show a relatively balanced trend in nitric acid recovery rate, total metal ion removal rate, and flux decline rate. Among them, Examples 3 and 4 show a more coordinated performance in acid recovery and stability. In the conventional single-variable comparative examples, deviations in imidazolium group content, high pressure differential, low water-to-material ratio, low crosslinking ratio, or large pore size will all worsen one or more of the following: acid recovery, metal ion control, or flux stability. In the synergistic comparative examples, after canceling crosslinking, canceling imidazoliumization, or disrupting the sequence of bromobutylation and quaternization, it is difficult to maintain the structural stability or acid mass transfer contribution simultaneously. This indicates that the matching of the crosslinked polybenzimidazole matrix and the imidazoliumized region helps to balance the inherently contradictory performance characteristics.
[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for treating and recovering waste nitric acid, characterized in that, Includes the following steps: S1, providing waste nitric acid solution, wherein the mass fraction of nitric acid in the waste nitric acid solution is 5-45 wt%, and the mass fraction of total metal ions based on metal elements is 0.05-15 wt%, wherein the total metal ions include at least one selected from divalent metal ions and trivalent metal ions; S2, the waste nitric acid feed solution is brought into contact with the feed side of the diffusion dialysis membrane module, and tap water is brought into contact with the dialysis side of the diffusion dialysis membrane module. The hollow fiber in the diffusion dialysis membrane module is obtained by polybenzimidazole, which is obtained by polycondensation of 3,3′-diaminobenzidine and isophthalic acid in polyphosphoric acid medium, crosslinked with 1,4-di(bromomethyl)benzene, bromobutylated with 1,4-dibromobutane, and further reacted with 1-methylimidazole. The content of imidazole onium groups in the hollow fiber is 0.30-1.20 mmol / g. S3 controls the processing temperature to be 20-45℃, the linear velocity of the feed liquid to be 0.20-1.00m / s, and the absolute value of the pressure difference between the dialysis side and the feed liquid side to be 0.01-0.15MPa, and uses a countercurrent method for mass transfer; S4, collect and recover acid solution and metal-rich residue solution respectively.
2. The processing and recycling method according to claim 1, characterized in that, The waste nitric acid solution originates from at least one of the processes of stainless steel pickling, metal surface treatment, post-nitration washing, or electronic chemical cleaning.
3. The processing and recycling method according to claim 1, characterized in that, Before step S1, the waste nitric acid solution is pre-filtered with a filtration accuracy of 1-100 μm; in step S2, the mass flow ratio of tap water to waste nitric acid solution is 1:1-6:1; steps S2 and S3 are carried out in the primary diffusion dialysis unit.
4. The processing and recycling method according to claim 1, characterized in that, The nitric acid recovery rate in step S4 is 70-95%, and the total metal ion removal rate is 60-95%. When the treatment and recovery method is run continuously for 100-500 hours, the flux decay rate of the diffusion dialysis membrane module is no higher than 20%.
5. The processing and recycling method according to claim 1, characterized in that, The diffusion dialysis membrane assembly used in step S2 includes a membrane shell and a hollow fiber membrane bundle disposed within the membrane shell. The hollow fiber membrane bundle is composed of multiple hollow fibers. Each hollow fiber includes a cross-linked polybenzimidazole matrix and imidazole-encapsulated regions covalently bonded to the cross-linked polybenzimidazole matrix. The hollow fibers have an inner diameter of 300-700 μm, a wall thickness of 100-220 μm, an imidazole-encapsulated group content of 0.30-1.20 mmol / g, and a water content of 7.0-17.0 wt%.
6. The processing and recycling method according to claim 5, characterized in that, The hollow fiber has an average pore size of 3-25 nm, a porosity of 15-45%, a water absorption rate of 8.0-20.0 wt%, and a burst pressure of 0.20-1.20 MPa; the thickness of the imidazole-encapsulated region is 20-120 nm; the effective membrane area of the diffusion dialysis membrane module is 0.1-20.0 m², and the membrane bundle packing density is 20-60%.
7. The processing and recycling method according to claim 5, characterized in that, The hollow fiber is prepared from the polybenzimidazole resin through the following steps: A1 is prepared by mixing 100 parts by weight of 3,3′-diaminobenzidine, 90-110 parts by weight of isophthalic acid, and 600-1200 parts by weight of polyphosphoric acid. A2 undergoes polycondensation at 180-220℃ for 6-14 hours under industrial nitrogen protection; A3. Pour the reaction product into deionized water to precipitate polybenzimidazole, and wash until the pH of the washing solution is 6-7. A4 was dried at 80-120℃ and under a vacuum degree not exceeding -0.08MPa for 8-24 hours to obtain polybenzimidazole resin with an intrinsic viscosity of 1.0-2.5dL / g.
8. The processing and recycling method according to claim 7, characterized in that, Cross-linked polybenzimidazole hollow fibers are prepared by the following steps: B1, dissolve the polybenzimidazole resin in N,N-dimethylacetamide to prepare a spinning solution with a polybenzimidazole mass fraction of 15-22 wt%, and degas for 1-8 hours; B2 is produced by dry-jet wet spinning under the following conditions: deionized water as the core liquid, spinning pressure of 0.05-0.30 MPa, air gap of 5-25 cm, coagulation bath of deionized water at 15-35 ℃, and traction speed of 3-5 m / min. B3, the polybenzimidazole hollow fibers are washed in deionized water until the residual N,N-dimethylacetamide is not higher than 1.0 wt%; B4, the washed polybenzimidazole hollow fibers are impregnated in a solution of N,N-dimethylacetamide containing 1,4-di(bromomethyl)benzene and reacted at 60-90°C for 1-6 hours under industrial nitrogen protection; B5 is washed and dried at 40-80℃ and a vacuum degree not higher than -0.08MPa for 4-24h to obtain cross-linked polybenzimidazole hollow fibers.
9. The processing and recycling method according to claim 8, characterized in that, The imidazole-enhanced region is formed through the following steps: C1, the cross-linked polybenzimidazole hollow fiber is impregnated in an N,N-dimethylacetamide solution containing 1,4-dibromobutane and reacted at 50-90°C for 1-8 hours under industrial nitrogen protection to introduce bromobutyl; C2, the cross-linked polybenzimidazole hollow fibers treated in step C1 are transferred to an N,N-dimethylacetamide solution containing 1-methylimidazole and reacted at 40-80°C for 2-12 hours to quaternize; C3, wash the cross-linked polybenzimidazole hollow fibers treated in step C2 until the bromide ion concentration in the washing solution is not higher than 50 mg / L; C4 is dried at 40-80℃ and a vacuum degree not higher than -0.08MPa for 4-24h to obtain imidazole-onthiolated crosslinked polybenzimidazole hollow fibers.
10. The processing and recycling method according to claim 8, characterized in that, In step B4, the molar ratio of 1,4-di(bromomethyl)benzene to benzimidazole NH in the polybenzimidazole hollow fiber before the reaction in step B4 is 0.02:1-0.20:1; in step C1, the molar ratio of 1,4-dibromobutane to benzimidazole NH in the crosslinked polybenzimidazole hollow fiber before the reaction in step C1 is 0.05:1-0.50:1; in step C2, the molar ratio of 1-methylimidazole to the bromobutyl group introduced in step C1 is 1.0:1-3.0:1.
Citation Information
Patent Citations
Diffusion dialysis membrane for recycling acid, as well as preparation method and application thereof
CN103962020A